An Observational Study To Asses The Role Of Acupuncture Points In Patients With Non-Specific Upper Limb Pain - Mahalwal, Neeti; Khan, Jafar; Pal, Renuka; Jain, Vardhman; Annamalai, K.M.; Pinjara, Farukh Mohammad; Jain, Presha; Khera, Neha; Menaria, Dinesh; Joshi, Jayesh (Journal of Neonatal Surgery, 2025)
Background:Non-specific upper limb pain is a common musculoskeletal issue with multifactorial etiology, including overuse, posture, and soft tissue dysfunction. While conventional physiotherapy has been effective, the incorporation of acupuncture-based approaches—especially stimulation of traditional acupoints—has shown promise in enhancing pain relief and functional recovery. Objective:To observe and evaluate the effectiveness of combining physiotherapy with acupressure (kneading of acupuncture points) in reducing pain and improving upper limb function in patients with non-specific upper limb pain. Methods:An observational study was conducted on 30 participants presenting with chronic non-specific upper limb pain. The intervention consisted of standard physiotherapy integrated with kneading techniques targeting traditional acupuncture points. Pain intensity was measured using the Visual Analog Scale (VAS), and functional ability was assessed with the Quick DASH questionnaire, both pre- and post-intervention. Statistical analysis was performed using the paired t-test, with significance set at p < 0.05. Results:Participants demonstrated a significant reduction in pain scores, with mean VAS decreasing from 5.79 ± 2.13 to 0.79 ± 0.77 (p < 0.001). Functional outcomes showed a dramatic improvement, with Quick DASH scores decreasing from 45.31 ± 15.71 to 3.81 ± 4.55 (p < 0.001). Improvements were consistent across age and gender categories, with no statistically significant differences between subgroups. Conclusion:The integration of acupuncture point stimulation (acupressure) with physiotherapy significantly improves outcomes in patients with non-specific upper limb pain. This observational study supports the therapeutic value of incorporating acupressure into routine physiotherapeutic management to accelerate recovery, reduce disability, and enhance quality of life. Further large-scale prospective studies are recommended to validate these findings